(untitled) (Palíndromo, 2026)
This article offers a critical reading of the sublime as an aesthetic and political category, examining its transformation from Romanticism to the Anthropocene. It aims to understand how the sublime, once associated with spiritual elevation in the face of natural vastness, has become today an experience of ecological consciousness and melancholy in response to environmental crises and the collapse between the natural and the artificial. The methodology combines historiographical and ecocritical analysis, drawing on authors such as Timothy Morton or Amanda Boetzkes, and juxtaposes theoretical texts with artistic practices that have shaped the imagination of wilderness. The findings indicate that the Romantic sublime, by idealising nature as external and pure, reinforced a form of green nostalgia and affective greenwashing, sustaining the separation between human and non-human. In contemporary contexts, this paradigm is replaced by a “techno-ruinous” sublime, characterised by awareness of planetary interdependence and ecological vulnerability. Thus the sublime should be reconceptualised as a critical device, capable of revealing the contradictions within the ecological imagination and promoting a post-natural ethics open to the reconfiguration of relationships between culture, technology, and ecology.